Indian Language Text Summarization Using Recurrent Neural Networks - Anjali, AV; Ramasubramanian, N; Santhanavijayan, A (International Journal of Computer Sciences and Engineering, 2025)
Text summarization is the process of creating short and accurate summary of a given text document. The paper is proposing an abstractive method of text summarization for text in Indian languages. The proposed algorithm uses an encoderdecoder recurrent neural networks with attention mechanism. The results observed were significantly better compared to the performance of already existing Indian language summarizer